Application of Electrocoagulation Process Using Iron and Aluminum Electrodes for Fluoride Removal from Aqueous Environment - Edris Bazrafshan; Kamal Aldin Ownagh; Amir Hossein Mahvi (E-Journal of Chemistry)
Fluoride in drinking water above permissible level is responsible for human being affected by skeletal fluorosis. The present study was carried out to assess the ability of electrocoagulation process with iron and aluminum electrodes in order to removal of fluoride from aqueous solutions. Several working parameters, such as fluoride concentration, pH, applied voltage and reaction time were studied to achieve a higher removal capacity. Variable concentrations (1, 5 and 10 mg L-1) of fluoride solutions were prepared by mixing proper amount of sodium fluoride with deionized water. The varying pH of the initial solution (3, 7 and 10) was also studied to measure their effects on the fluoride removal efficiency. Results obtained with synthetic solution revealed that the most effective removal capacities of fluoride could be achieved at 40 V electrical potential. In addition, the increase of electrical potential, in the range of 10-40 V, enhanced the treatment rate. Also comparison of fluoride removal efficiency showed that removal efficiency is similar with iron and aluminum electrodes. Finally it can be concluded that the electrocoagulation process has the potential to be utilized for the cost-effective removal of fluoride from water and wastewater.